The effect of sago starch (Metroxylon sp.) and chitosan as edible coating on physical and chemical characteristics of red chili (Capsicum annuum L.) - Islami, Iasha Fahira; Rahmadhia, Safinta Nurindra (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
The reduced quality of red chili can be attributed to moisture loss. To inhibit water vapor transfer, one effective method is using an edible coating. This study aims to determine the effects of sago starch and chitosan as coating materials in reducing chili deterioration during storage at room temperature. A one-factorial, completely randomized design was used, with variations in the ratios of sago starch to chitosan (76.19%:23.81%, 71.43%:28.57% and 66.67%:33.33%). The parameters tested included weight loss, hardness, color, and moisture content. Red chili storage was conducted at room temperature, with observations on days 1, 3, 6, 9, 12, and 15. The results indicated that the edible coating made from sago starch and chitosan significantly impacted the weight loss, hardness, color, and moisture content of the red chili. The best treatment for maintaining the physical and chemical properties of red chili during room temperature storage was the 66.67% sago starch and 33.33% chitosan formulation, which resulted in a weight loss of 46.99%, hardness of 35.01 N, color a* value of 30.60%, color b* value of 20.90%, brightness L* value of 26.11%, and moisture content of 67.92%.